Modeling and simulation of pure electric vehicle composite power supply. Issue 1 (1st October 2022) - Zheng, Jintang; Fu, Qiye; Zhou, Heng; Liu, Wei
Abstract: In order to solve the problem of high discharge current, serious heating and low service life of pure electric vehicle with single power battery system driving at high power. Design a top-level model of the composite power supply with battery and ultra-capacitor for pure electric vehicles in the simulation software ADVISOR, propose an energy management control strategy based on logic threshold control theory. Based on MATLAB/Simulink environment, set up a logic threshold limit filtering power shunt module and chose the working condition of NEDC for simulation. The results show that, compared to single battery system, a composite power system embedded in the logic threshold control strategy of filtering thought can distributes the power between the battery and the ultra-capacitor more reasonably, effectively improves the peak output power of the battery, avoiding high current charge and discharge of batteries, extends the life of the battery, and improve the vehicle's power and economy.